Turning up the volume: a study of the Wan Smolbag Theatre Company - Robin Taylor; Ian Gaskell (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
﻿Research with a highly successful development theatre company „Wan Smolbag‟, based in Vanuatu in the South Pacific, was conducted to establish why they have remained effective and successful for almost two decades. Wan Smolbag appear to be engaging in a number of different literacies simultaneously. Theatre performance as one kind of literacy is not part of the traditional ethnic culture. Likewise the development literacies that are associated with the process of modernisation are new to the people of Vanuatu. Semi-structured interviews and focus group discussions were recorded and transcribed. We used a thematic analysis to highlight and bring out common themes. The results suggest that one of the principle reasons that the company themselves believe why it is that they have remained effective, is because of their attention to the „art‟ in their performance rather than merely he „message‟. Implications for the implementation of Theatre for Development are discussed.